Pedagogical Approach to Entrepreneurship Success: Innovation in Training - Seow, Richard (Research in Management of Technology and Business, 2023)
Entrepreneurship is a challenging and rewarding venture where only a small number of entrepreneurs succeeded. There are multiple factors influencing the success of an entrepreneur. This case is about Eric Chua, an entrepreneur, who had devoted thirty years to build a successful insurance agency. Eric started his life insurance business in 1992 with the aim to improve his financial situation and pay off his debts. Although he was promoted to agency manager in 1998, he only set up his own insurance agency, the RFS Partners (TRP), in 2006. They agency with two managers and RM2 million in new business annually. In 2022, they have managed to grow TRP to five managers and more than RM10 million in new business annually. One of the business innovations that Eric developed which supported the business growth is TRP’s training system. Agent development is fundamental to the success of an insurance agency and without an effective training system, not only developing successful life insurance agents (LIAs) will be challenging, any successful approach cannot be duplicated as well. Eric understands the importance of formulating an effective training system and has been working on improving the training system since 2006. After many years of hard work, the current TRP’s training system was developed and had contributed significantly to the growth of TRP.